(untitled) (Research, Society and Development, 2020)
A River basin play a fundamental role in territorial development whereas the exploitation of natural resources is balanced both by the population and competents institutions. Thus, the objective of this research was to automatically delimit and calculate the average rainfall of the Rio Mundaú River Basin (BHRM). The image was processed in the free software QGIS 2.18.7 using the set of tools embedded in TauDEM (Terrain Analysis Using Digital Elevation Models) that dimension the entire hydrological mesh through the use of MDE’s (Digital Elevation Model) from altimetric image data SRTM (Shuttle Radar Topographic Mission). It was developed the modeling of the drainage network, observing the removal of depressions, slopes, main channel, directions of simple and multiple flows. Then, after the hydrological delimitation and calculation of the BHRM area, the average precipitation was calculated using the Thiessen method with subsidy of pluviometric data collected in meteorological stations present in the perimeter of the basin. To complement the work, some characterizations were made using the obtained MDE and thus corroborating the interpretation of the results. Significant differences in BHRM’s rainfall indexes were found between between the period of 2013 to 2019, since at the beginning of the observation, the state of Pernambuco and Alagoas had been going through a significant drought period, thus justifying the reduced rainfall volume. Regarding the computation of the area, there was a difference of more than 400 km² in the BHRM area when correlated with information from official agencies, that is, a reduction of approximately 10%.